2020
DOI: 10.1186/s12887-020-02324-1
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of neonates with tracheostomy secondary to bronchopulmonary dysplasia

Abstract: Background: Bronchopulmonary dysplasia (BPD) is a disease that can affect preterm neonates. Infants with severe BPD may develop pulmonary hypertension (PHN) and may require chronic mechanical ventilation with tracheostomy. The outcomes of these infants have not been studied well. We proposed to review survival and outcomes of infants requiring tracheostomy secondary to severe BPD in our NICU at 24 months. Methods: We reviewed infants' charts who were diagnosed with BPD that underwent tracheostomy from January … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 27 publications
2
32
0
Order By: Relevance
“…In comparison to other contemporary reports where tracheostomy placement occurred at a mean~45-51 weeks' CGA, tracheostomy placement at our institution was markedly earlier. 16,18,23,26 Furthermore, our timing of~120 days is at the threshold of the earlier window identified by the NRN as associated with a~50% reduction in the risk of death or neurodevelopmental impairment. 19 Indeed, compared to infants that survived, infants in our cohort that died received their tracheostomy significantly later (45.5 vs. 42.5 weeks' CGA, p < .03).…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…In comparison to other contemporary reports where tracheostomy placement occurred at a mean~45-51 weeks' CGA, tracheostomy placement at our institution was markedly earlier. 16,18,23,26 Furthermore, our timing of~120 days is at the threshold of the earlier window identified by the NRN as associated with a~50% reduction in the risk of death or neurodevelopmental impairment. 19 Indeed, compared to infants that survived, infants in our cohort that died received their tracheostomy significantly later (45.5 vs. 42.5 weeks' CGA, p < .03).…”
Section: Discussionmentioning
confidence: 83%
“…Death before initial discharge was most often the result of worsening pulmonary disease, and similar to previous reports, infants that were born SGA and/or receiving therapy for pulmonary hypertension as the time of tracheostomy suffered increased mortality. 17,18,28,29 Infants born SGA are at greater risk of severe BPD and death, and pulmonary hypertension has been independently associated with increased risk of mortality in premature infants with BPD. [30][31][32][33][34][35][36] Murthy et al 17 demonstrated that infants born at <32 weeks' gestation with severe BPD complicated by pulmonary hypertension had three times increased risk of tracheostomy or death.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although chronic ventilation may give an infant with sBPD the best chance at a positive outcome, survival is not always possible 44,45 . In preterm infants with neuromuscular and congenital heart diseases, mortality before initial discharge has been described to be as high as 40% 46 .…”
Section: Transition From the Intensive Care Unit (Icu) Ventilator To A Home Ventilatormentioning
confidence: 99%
“…Indeed, neonates with subglottic stenosis may not tolerate extubation and are at high risk of undergoing tracheotomy. (20,59) Management of subglottic stenosis in neonates with BPD should focus on prevention. Recent efforts have increased the use of nasal CPAP at birth rather than intubation to minimize the risk of the development of BPD.…”
Section: Subglottic Stenosismentioning
confidence: 99%